Factors that Influence Adoption of New Improved Wheat Varieties by Farmers in Nakuru and Narok, Kenya - Gichangi, Ann; Mukhebi, Adrian; Murithi, Festus (European Journal of Agriculture & Food Science, 2022)
This study examines the factors that influence the adoption of new improved wheat varieties (NIWV) by wheat farmers in Nakuru and Narok counties in Kenya. Cross-sectional data from 344 randomly selected wheat farmers from the Njoro and Rongai sub-Counties in Nakuru County; and Narok South and Narok North sub-counties in Narok County, Kenya were investigated. Probit model was run to estimate the factors influencing the adoption rate of improved new wheat varieties. Results derived from model estimates indicate that farmers' adoption of improved wheat varieties in the study area is positive due to education, availability of information, off-farm income, distance to inputs and produce markets, and exposure to extension advice services and access to credits. The study recommends that the public and private sectors promote access to advisory services to improve the dissemination of certified wheat seeds to farmers through training, workshops, and seminars.
Keywords: Adoption; Kenya; New Improved Varieties; Wheat